(untitled) - Kegley, Charles W. (Boston, 2001)
A reader by top scholars; The Global Agenda is incisive in its coverage of key concepts, issues and theoretical and prescriptive approaches to the interpretation of world politics. The readings in this top selling book are broad based, balanced, and are categorized into four areas that build on the distinction between high and low politics.
Keywords: International relations,International economic relations,Globalization,World politics; 1989-